Comparison of Efficacy and Outcome of Minimally Invasive versus Open Surgery for Intradural-Extramedullary Spine Tumors: Systematic Review - Putra, Yosie Yulanda; Lestari, Deby Tri; Auliya, Ahsan; Ananda, Astrid; Syarfina, Afdila; Azhari, Ririn; Merisa L, Bella (The International Journal of Medical Science and Health Research, 2024)
Background:  While traditional wide-incision approaches pose risks of long-term spinal instability, minimally invasive techniques, increasingly favored since the late 1990s, require further investigation regarding their safety and efficacy compared to open approaches for Intradural extramedullar (ID-EM) tumor resection. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Employing a meticulous three-tier screening approach, we identified only five papers that were directly pertinent to our ongoing systematic assessment. Subsequently, we conducted a comprehensive examination of the entire text and further selected articles; retrospective study, retrospective analysis, retrospective observational study; comparative, prospective cohort, and retrospective cohort study. Conclusion: The minimally invasive transspinous approach demonstrates safety and efficacy comparable to open surgery, with reduced intraoperative blood loss, but further randomized studies are needed to assess their cost-effectiveness and wider adoption. Although minimally invasive tubular retractor surgery shows favorable outcomes, particularly in reducing postoperative paraspinal muscle fatty degeneration and analgesic consumption, larger studies are warranted to confirm its long-term effects on pain reduction and patient outcomes. As these techniques gain traction, their potential benefits in improving patient care will become increasingly apparent.